Perancangan Sign System Kawasan Outbound Edukasi Satwa, Agro & Perikanan di Alas Outbound Prambon - Tirta Adi Nugraha; Sri Wulandari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Alas Outbound is an educational tourist destination in Simpang village, Prambon District, Sidoarjo regency, which offers various facilities and activities, such as playground rides, swimming pools, fish ponds, mud ponds, and education about animals, plantations, Fisheries, and natural scenery. The Merdeka Campus Competition Program (PKKM) of the Visual Communication Design Education Program of the National Development University